Technological Pedagogical Content Knowledge of a Computer Engineering Professor. A collaborative case study with the perspective of Professor and Researchers - Adriana Gewerc Barujel; Eulogio Pernas Morado; José Varela Pet (Universitat Politècnica de València, 2013)
The framework of this paper is a coordinated research project between three universities (Barcelona, Sevilla and Santiago de Compostela) entitled: Professional knowledge of university professors: the Construction and transfer of teaching practice2 . It is based on an unexplored higher education theoretical approach: analysis of pedagogical content knowledge (PCK), an original Shulman (1986) construct that Mishra and Koehler (2006) extended to Technological Pedagogical Content Knowledge (TPCK). It is a multiple case study. Each university took three cases of three professors selected as good teachers. We focus here on the case of a teacher of the Degree in Computer Engineering from the School of Engineering at University of Santiago de Compostela (USC). Non participant observation of classes and in-depth interviews were carried out. Data were analyzed based on theoretical dimensions and those arising from the observations. This paper presents the dimension "transformation of knowledge" that allows realizing the teacher's TPCK, and a dialogue between the teacher who was the own "case" and two USC researchers. This crossing perspective is around two issues: the relationship between teaching and research and TCPK. The results show limited relationship between research and teaching and poor use of specific technologies to help students understand the subject.